Work-related Health Problems in Emergency Health Services Workers - Levent Şahin; Ali Gur; Muhammed Ekmekyapar; Mehmet Ali Bilgili (Van Tıp Dergisi, 2021)
INTRODUCTION: In this study, it was aimed to investigate the physical, psychological and familial problems of the healthcare provider working in emergency health care services that develop due to their work and working conditions. METHODS: 297 people working in emergency health services in three different cities were included in the study. The study was carried out between November 15 and December 15, 2020 by conducting an online questionnaire. The participants in the study were asked questions about their physiological and psychological health conditions through the questionnaire. The answers received were evaluated statistically. RESULTS: In this study conducted with 297 people working in emergency health services (EHS), 189 (63.6%) people had health problems, 249 (83.8%) people worked even though they were ill, 186 (62.6%) people did not go to regular check-ups about their diseases, 282 (94.9%) were found to be under occupational stress and 141 (47.5%) of them needed psychological support. It has been determined that women have more health problems than men, are constantly using medication and need psychological support more (p=0.002, p=0.001, p=0.001). The health status of EHS employees who worked on duty was worse than those working overtime. This situation was statistically significant (p=0.002). DISCUSSION AND CONCLUSION: It is observed that emergency health care workers have some physical and mental problems. All stressful situations on healthcare provider should be identified and working conditions should be improved.